Plasmonic Sensors: A New Frontier in Nanotechnology - Kumar, Samir; Seo, Sungkyu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers the theory and fabrication of plasmonic nanostructures, patterned surfaces, and devices for lossy mode resonance (LMR), surface plasmon resonance (SPR), surface-enhanced fluorescence spectroscopy (SEFS), and surface-enhanced Raman scattering (SERS)-based biosensors. The chapters in this reprint cover a range of topics, including the interplay between SPR and lossy mode resonance, fabrication of LSPR substrates using high-throughput techniques, recent advances in various nanostructures, recent developments in the field of nanostructured Ag substrates, and innovative advances in biosensors based on DNA nanotechnology. These chapters provide a comprehensive overview of recent developments in plasmonic biosensors, making this reprint essential reading for researchers working in biosensors and plasmonics.